Adenovirus-mediated expression of BMP-7 suppresses the development of liver fibrosis in rats. Issue 5 (24th November 2006) - Kinoshita, Kohji; Iimuro, Yuji; Otogawa, Kohji; Saika, Shizuya; Inagaki, Yutaka; Nakajima, Yuji; Kawada, Norifumi; Fujimoto, Jiro; Friedman, Scott L; Ikeda, Kazuo
Abstract : Background: Liver cirrhosis, which is caused by the accumulation of extracellular matrix materials, is a serious clinical problem that can progress to hepatic failure. Transforming growth factor-β (TGFβ) plays a pivotal role in extracellular matrix production, but bone morphogenetic protein (BMP)-7, a member of the TGFβ superfamily, can antagonise the fibrogenic activity of TGFβ. Aim: In this study, we examined whether adenovirus-mediated overexpression of BMP-7 (Ad-BMP-7) antagonised the effect of TGFβ in vitro and in vivo. Methods and results: In primary cultured rat stellate cells and the LX-2 human stellate cell line, induction of BMP-7 by Ad-BMP-7 infection decreased the expression of collagen 1A2 mRNA and smooth muscle α-actin in the presence or absence of TGFβ, via Smad 1/5/8 phosphorylation. BMP-7 triggered the mRNA expression of inhibitors of differentiation 2 (Id2) in LX-2. Although endogenous expression of BMP-7 was hardly detectable, Smad1 and Id2 overexpression increased BMP-7 expression in LX-2. A liver fibrosis model was induced by the repetitive intraperitoneal injection of thioacetamide (200 mg/kg body weight) twice per week for up to 7 weeks. In rats administered Ad-BMP-7 via the tail vein, hydroxyproline content and the areas stained by Sirius red dye in the liver were significantly reduced compared to controls. Ad-Id2 also reduced fibrosis. Conclusion: These data demonstrate that BMP-7, Smad 1/5/8 and Ids interact to antagonise hepatic fibrogenesis.